The Effectiveness Of Batubara's Consumers Disputes Resolution Agency In Consumers Disputes Resolution - Purnama Hidayah Harahap (Institut Agama Islam Negeri Padngsidimpuan, 2020)
AbstractThe mismatch between consumers and producers can cause large potential disputes.The disputes can be resolved outside of the court through the Consumers Disputes Settlement Agency in accordance with Law No. 8 of 1999 concerning consumers protections. The qualitative descriptive method used in this study aims to examine the status of human groups, circumstances or conditions that are not manipulated or normal and natural. The purpose of this research is to find out the obstacles of BPSK in implementing UUPK and investigate the necessary coordination procedures. The results of the study found that the obstacles that hamper BPSK's performance in providing consumers rights protection in accordance with their duties and authority are the quality of human resources, human resources competence where almost 50% of BPSK workers were non-law majors, small funding factors, the lack of assets and knowledge of the community and other institutions about BPSK. AbstrakKetidakselarasan antara konsumen dan pelaku bisnis dapat menyebabkan potensi sengketa yang sangat besar. Dalam hal ini perselisihan dapat diselesaikan di luar pengadilan yaitu oleh Badan Penyelesaian Sengketa Konsumen menurut UndangUndang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Metode deskriptif kualitatif digunakan dalam penelitian ini bertujuan untuk memeriksa status kelompok manusia, keadaan atau kondisi yang tidak dimanipulasi atau normal dan alami. Tujuan penelitian ini untuk mengetahui hambatan BPSK dalam mengimplementasikan UUPK, menyelidiki prosedur koordinasi yang diperlukan. Hasil penelitian ditemukan bahwa kendala yang menjadi penghambat kinerja BPSK dalam memberikan perlindungan hak-hak konsumen sesuai dengan tugas dan wewenangnya adalah kualitas sumber daya manusia, Kompetensi perangkat hampir 50% staf memiliki pendidikan sarjana non-hukum, faktor pembiayaan atau alokasi anggaran yang kecil dan kurangnya aset. kurangnya pengetahuan masyarakat dan lembaga lain tentang BPSK.